ANALISIS PENGARUH AKUNTANSI KEBERLANJUTAN TERHADAP KINERJA KEUANGAN DI PERUSAHAAN YANG TERDAFTAR PADA IDX 30 BURSA EFEK INDONESIA - KOTIMAH, KUSNUL; HATUMENA, GRACE LORDITA; NATALIA, YOHANA FRANSISKA; PANDIN, MARIA YOVITA R. (GANEC SWARA, 2024)
The aim of this research is to determine the effect of sustainability accounting on financial performance in companies listed on the Indonesia Stock Exchange. The object of this research is the IDX 30 company on the Indonesian Stock Exchange in 2021-2022. The type of research used is quantitative descriptive research. The data used uses secondary data, so the data collection technique used by researchers is by searching, studying and analyzing company documents or data. The data obtained is in the form of soft copies of annual financial reports and also sustainability reporting reports obtained from the official websites of registered companies. on the Indonesian Stock Exchange. The data analysis method in this research uses hypothesis data testing in the form of SPSS (Statistical Package For The Social Sciences) with a descriptive statistical test approach, classical assumptions, and multiple linear regression analysis. The research results obtained are that accounting accounting as measured by three aspects, namely economic, environmental and social, does not have a significant positive effect on financial performance as measured by Return on Assets